Nutritional adequacy of different menu settings in elite Spanish adolescent soccer players - Garrido, G.; Webster, A. L.; Chamorro, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The article describes a study that evaluated the adequacy of 2 different menu settings in a group of elite adolescent Spanish soccer players. Five-day food intake was assessed on 2 occasions, while athletes were consuming a flexible "buffet-style" diet (B; n = 33) and a fixed "menu-style" diet (M; n = 29). For all principal meals of the day food weighing was performed, and snacks were recorded by self-report. M provided significantly higher total energy and carbohydrate intakes than B. Breakfast and snacks both provided more energy in M. Calories obtained from fat were excessive in both settings. Calcium and vitamin D were below recommendations in B but not in M. Fiber, magnesium, folate, vitamin A, and vitamin E intake fell below recommended values in both settings. M provided significantly greater quantities of magnesium and vitamins D and E. Both feeding options were far from optimal in satisfying current scientifically based recommendations for active adolescents.